Evolutionary and Regulatory Pattern Analysis of Soybean Ca2+ ATPases for Abiotic Stress Tolerance - Wang, Jian; Fu, Xujun; Zhang, Sheng; Chen, Guang; Li, Sujuan; Shangguan, Tengwei; Zheng, Yuanting; Xu, Fei; Chen, Zhong-Hua; Xu, Shengchun (Frontiers in Plant Science, 2022)
P2-type Ca2+ ATPases are responsible for cellular Ca2+ transport, which plays an important role in plant development and tolerance to biotic and abiotic stresses. However, the role of P2-type Ca2+ ATPases in stress response and stomatal regulation is still elusive in soybean. In this study, a total of 12 P2-type Ca2+ ATPases genes (GmACAs and GmECAs) were identified from the genome of Glycine max. We analyzed the evolutionary relationship, conserved motif, functional domain, gene structure and location, and promoter elements of the family. Chlorophyll fluorescence imaging analysis showed that vegetable soybean leaves are damaged to different extents under salt, drought, cold, and shade stresses. Real-time quantitative PCR (RT-qPCR) analysis demonstrated that most of the GmACAs and GmECAs are up-regulated after drought, cold, and NaCl treatment, but are down-regulated after shading stress. Microscopic observation showed that different stresses caused significant stomatal closure. Spatial location and temporal expression analysis suggested that GmACA8, GmACA9, GmACA10, GmACA12, GmACA13, and GmACA11 might promote stomatal closure under drought, cold, and salt stress. GmECA1 might regulate stomatal closure in shading stress. GmACA1 and GmECA3 might have a negative function on cold stress. The results laid an important foundation for further study on the function of P2-type Ca2+ ATPase genes GmACAs and GmECAs for breeding abiotic stress-tolerant vegetable soybean.